AN ANALYSIS OF ONLINE GAMES’ EXPOSURE TOWARDS STUDENTS’ ENGLISHVOCABULARY - Delfita Yulianti; Irwandi Irwandi (International Journal of Teaching and Learning, 2025)
This literature review analyses the effects of online games to the acquisition of students’ vocabulary in English. In order to become competent and proficient in a second language, vocabulary knowledge is essential. It is a crucial skill that students studying English as a Second Language (ESL) must acquire because understanding written and spoken communication requires a large vocabulary. Due to the general consensus that educational online games can enhance the learning process, the use of these games in vocabulary instruction is becoming more and more common. Based on library research, this study offers a review of the literature on the topic of vocabulary acquisition related to online games for ESL students. The research has demonstrated the potential of online games as learning aids for vocabulary since they increase student satisfaction with their studies and encourage independent learning.